Primordial Fluctuations From Quantum Gravity - Gozzini, Francesco; Vidotto, Francesca (Frontiers in Astronomy and Space Sciences, 2021)
We study the fluctuations and the correlations between spacial regions generated in the primordial quantum gravitational era of the universe. We point out that these can be computed using the Lorentzian dynamics defined by the Loop Quantum Gravity amplitudes. We evaluate these amplitudes numerically in the deep quantum regime. Surprisingly, we find large fluctuations and strong correlations, although not maximal. This suggests the possibility that early quantum gravity effects might be sufficient to account for structure formation and solve the cosmological horizon problem.